2010
DOI: 10.3892/or_00000749
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic pancreatic cancer: Is gemcitabine still the best standard treatment? (Review)

Abstract: Abstract. Pancreatic ductal adenocarcinoma is the fourth cause of death in the Western world. Surgery remains the only treatment offering an advantage in terms of overall survival (5-year survival range, 15-25%), but unfortunately only 10-20% of patients present resectable disease at the time of diagnosis. Hence chemotherapy, possibly combined with radiation therapy, remains the only treatment option aimed at palliation of symptoms and ensuring a better quality of life. Notwithstanding the efforts to find more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 102 publications
2
83
0
Order By: Relevance
“…While many primary tumors can be eradicated by surgery if detected early in the course of disease progression, the appearance of metastatic disease is associated with a poor prognosis that worsens with the development of resistance to conventional chemotherapies (O'Day and Gorlick, 2009;Box et al, 2010;Verma et al, 2011). In the past ten years, there has been a frustrating lack of clinical advancements in the treatment of metastatic cancers (Di Marco et al, 2010, Stathis and Moore, 2010, Nieto et al, 2008. Once metastatic disease develops in pediatric sarcomas or in breast cancer, for 3.…”
Section: Setting the Stage -Targeting Metastasis One Of The Gravest mentioning
confidence: 99%
“…While many primary tumors can be eradicated by surgery if detected early in the course of disease progression, the appearance of metastatic disease is associated with a poor prognosis that worsens with the development of resistance to conventional chemotherapies (O'Day and Gorlick, 2009;Box et al, 2010;Verma et al, 2011). In the past ten years, there has been a frustrating lack of clinical advancements in the treatment of metastatic cancers (Di Marco et al, 2010, Stathis and Moore, 2010, Nieto et al, 2008. Once metastatic disease develops in pediatric sarcomas or in breast cancer, for 3.…”
Section: Setting the Stage -Targeting Metastasis One Of The Gravest mentioning
confidence: 99%
“…Many phase II trials have demonstrated the efficacy of gemcitabine-based combinations, which comprise other cytotoxic molecules such as capecitabine, 5-FU, cisplatin, irinotecan [34][35][36][37] or the targeted agents sorafenib and cetuximab [38][39][40] . However, in some randomized phase III trials of gemcitabine based chemotherapy combinations, these combinations failed to show statistically significant improvement in patient's overall survival when compared to gemcitabine used as a single-agent [41][42][43][44][45][46] .…”
Section: Chemotherapy Gemzar -Gemcitabinementioning
confidence: 99%
“…Activated EGFR forms homo-or heterodimeric complexes with other members of the ErbB family, triggering downstream signaling pathways such as Ras/MAP kinase, phosphatidylinositol 3'-kinase (PI3K)/Akt, Janus kinase (JAK)/Stat and phospholipase C/protein kinase C, that ultimately activate genes involved in cell proliferation, migration, adhesion, differentiation and apoptosis (Di Marco et al, 2010). Overexpression of EGFR and its ligands is very common in pancreatic cancer, and it is linked to increased tumor aggressiveness and poor prognosis.…”
Section: Egfr-ras-mek-erk Pathwaymentioning
confidence: 99%